Molecular dynamics-guided titanium platform with chitosan-assisted bacterial anchoring for sequential antibacterial and osteogenic functions - Jiaying Li; Junkai Hu; Jiamin Li; Weihan Zheng; Jiejie Wang; Tao Lin; Jiahao Pu; Tingting Chen; Mingrui Li; Hang Sang; Jianlin Shen; Lincong Luo; et al. (Chemical Engineering Journal, 2026)

From one base-year map to long-term paddy rice maps: an unsupervised transfer learning framework - Haoyue Jiang; Yang Zhou; Jie Song; Meng Xu; Junkai Ma; Jiaqi Song; Lin Zhu; Yanyan Shi; Jinyan Tian (International Journal of Remote Sensing, 2026)

Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Application and geometric optimization analysis of hydrofoils during descent with mission payloads - Zhengwei Wang; Haitao Gu; Yang Lin; Lin Xing; Junkai Cao; Hangqing You (Ocean Engineering, 2026)

Chlorinated and brominated persistent organic pollutants in industrial thermal processes: Emission profiles and radical-mediated formation pathways - Junkai Lin; Bingcheng Lin; Zhiyuan Xu; Guohua Zhu; Rong Jin; Lyumeng Ye; Dongyao Chen; Xin Zhou; Minghui Zheng (Journal of Environmental Sciences, 2026)

3D-printed Li-HA composite scaffold with staged simvastatin/NGF delivery and continuous Li+ signaling enhances immune–neuro–angiogenic coupling for bone repair - Xianglei Mo; Tengbin Shi; Siyi Huang; Dongyi Mai; Lingyu Kong; Junkai Mi; Zongqiang Gao; Wenge Liu; Yanjin Lu; Tingting Huang; Jinxin Lin (Chemical Engineering Journal, 2026)

Large-Scale Plasma Proteomics Profiles for Predicting Atrial Fibrillation Associated Stroke Risk - Shengkang Huang; Xin Feng; Huilin Wu; Rongxuan Liang; Yuan Gao; Zhaojun Wang; Botao Tang; Jiatong Wu; Junkai Fang; Ziang Yang; Xieraili Tiemuerniyazi; Jiancheng Lin; et al. (Translational Stroke Research, 2026)

3D-printed porous titanium alloy scaffolds modified with composite hydrogel-loaded emodin liposomes for the treatment of periprosthetic joint infection - Jiamin Li; Jiaying Li; Junkai Hu; Tingting Chen; Tao Lin; Jiahao Pu; Lincong Luo; Wenhua Huang (Chemical Engineering Journal, 2026)

Neural network based on high freedom dynamic collaboration of flows for meteorological data temporal downscaling - Junkai Wang; Yu Zhang; Shuangrui Liu; Lianlei Lin; Qiong Li; Zongwei Zhang; Hanqing Zhao; Hangyi Yu; Yupu Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Feasibility-guided search and prediction for dynamic constrained multiobjective evolutionary optimization - Lisha Dong; Qianhui Wang; Qiongfang Liu; Junkai Ji; Ka-Chun Wong; Qiuzhen Lin (Swarm and Evolutionary Computation, 2025)

Bioaugmentation with Zymomonas mobilis modulates microbial succession and enhances volatile profiles in strong-flavor Daqu fermentation - Hanrui Lin; Linpei Liu; Yong Zhuang; Bo Wu; Junkai Ma; Yiran Ma; Mingxiong He (International Journal of Food Microbiology, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Spatiotemporal UNet for multi-field spatiotemporal series generation - Lianlei Lin; Sheng Gao; Zongwei Zhang; Hanqing Zhao; Junkai Wang (International Journal of Remote Sensing, 2025)

Removal of ofloxacin and inhibition of antibiotic resistance gene spread during the aerobic biofilm treatment of rural domestic sewage through the micro–nano aeration technology - Bingbing Feng; Juan Chen; Chao Wang; Peifang Wang; Guoxiang You; Junkai Lin; Han Gao (Journal of Hazardous Materials, 2025)

Distribution of long-chain polyunsaturated fatty acids and the effects of molasses on DHA production in Thraustochytrium sp. 26185 - Xi Xie; Ziwei Guo; Qinghua Mo; Junkai Luo; Li Lin; Huifan Liu; Gengsheng Xiao; Qin Wang (Algal Research, 2025)

Generating logic circuit classifiers from dendritic neural model via multi-objective optimization - Haochang Jin; Chengtao Yang; Junkai Ji; Jin Zhou; Qiuzhen Lin; Jianqiang Li (Swarm and Evolutionary Computation, 2024)

Evaluation of six phenolic compounds content and antifungal activity against wood-decay fungi of tobacco waste extracts obtained by ultrasound-assisted extraction - Lin Liu; Jun Li; Junkai Tian; Ziyao Zhou; Jingran Gao; Lei Qin; Jian Qiu (Sustainable Chemistry and Pharmacy, 2024)

Deep neural network based on dynamic attention and layer attention for meteorological data downscaling - Junkai Wang; Lianlei Lin; Zongwei Zhang; Sheng Gao; Hangyi Yu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

The influence of displacement ventilation on indoor carbon dioxide exposure and ventilation efficiency in a living laboratory open-plan office - Yalin Lu; Junkai Huang; Danielle N. Wagner; Zhang Lin; Nusrat Jung; Brandon E. Boor (Building and Environment, 2024)

Ofloxacin weakened treatment performance of rural domestic sewage in an aerobic biofilm system by affecting biofilm resistance, bacterial community, and functional genes - Bingbing Feng; Juan Chen; Chao Wang; Guoxiang You; Junkai Lin; Han Gao; Shanrui Han; Junchao Ma (Environmental Research, 2024)

Injectable hydrogel microspheres encapsulating extracellular vesicles derived from melatonin-stimulated NSCs promote neurogenesis and alleviate inflammation in spinal cord injury - Junkai Zeng; Changjiang Gu; Yu Zhuang; Kaili Lin; Youzhuan Xie; Xiongsheng Chen (Chemical Engineering Journal, 2023)

Bifunctional lithiophilic carbon fibers with hierarchical structure for high-energy lithium metal batteries - Taiyu Lyu; Fenqiang Luo; Zhen Wang; Futing Jiang; Shize Geng; Yan Zhuang; Xin Lin; Junkai Chen; Dechao Wang; Lingzheng Bu; Lei Tao; Lizhe Liang; et al. (Chemical Engineering Journal, 2023)

A novel molecular docking program based on a multi-swarm competitive algorithm - Jin Zhou; Zhangfan Yang; Ying He; Junkai Ji; Qiuzhen Lin; Jianqiang Li (Swarm and Evolutionary Computation, 2023)

Exposure of ambient PM2.5 during gametogenesis period affects the birth outcome: Results from the project ELEFANT - Liqiong Guo; Huishu Lin; Hongyu Li; Xiaobin Jin; Lei Zhao; Penghui Li; Naiwei Xu; Song Xu; Junkai Fang; Shaowei Wu; Qisijing Liu (Environmental Research, 2023)

Physical and Numerical Investigations on Wave Run-Up and Dissipation under Breakwater with Fence Revetment - Enjin Zhao; Lin Mu; Zhaoyang Hu; Xinqiang Wang; Junkai Sun; Zhiyong Zhang (Journal of Marine Science and Engineering, 2021)
Revetment elements and protective facilities on a breakwater can effectively weaken the impact of waves. In order to resist storm surges, there is a plan to build a breakwater on the northern shore of Meizhou Bay in Putian City, China. To better design it, considering different environmental conditions, physical and numerical experiments were carried out to accurately study the effects of the breakwater and its auxiliary structures on wave propagation. In the experiments, the influence of the wave type, initial water depth, and the structure of the fence plate are considered. The wave run-up and dissipation, the wave overtopping volume, and the structure stability are analyzed. The results indicate that the breakwater can effectively resist the wave impact, reduce the wave run-up and overtopping, and protect the rear buildings. In addition, under the same still water depth and significant wave height, the amount of overtopped water under regular waves is larger than that under irregular waves. With the increase of the still water depth and significant wave height, the overtopped water increases, which means that when the storm surge occurs, damage on the breakwater under the high tide level is greater than that under the low tide level. Besides, the fence plate can effectively dissipate energy and reduce the overtopping volume by generating eddy current in the cavity. Considering the stability and the energy dissipation capacity of the fence plate, it is suggested that a gap ratio of 50% is reasonable.

Resource Status and Effect of Long-Term Stock Enhancement of Large Yellow Croaker in China - Jigui Yuan; Hungdu Lin; Lisheng Wu; Xuan Zhuang; Junkai Ma; Bin Kang; Shaoxiong Ding (Frontiers in Marine Science, 2021)
The large yellow croaker, Larimichthys crocea , was once the most abundant and economically important marine fish in China. Thus far, it has also been the most successful mariculture fish species in China. However, its wild stock severely declined in the 1970s because of overexploitation, and therefore hatchery release has been carried out for stock enhancement since 2000. As a migratory fish, large yellow croaker was divided into three geographical stocks according to ambiguous morphological and biological characteristics in early documents. To investigate the identity of wild large yellow croaker populations and assess the influence of hatchery supplementation on wild populations, a total of 2,785 cultured individuals and 591 wild individuals were collected from 91 hatcheries and six wild populations along the coast of mainland China and analyzed using two mitochondrial genes [cytochrome oxidase I ( COI ) and cytochrome b ( Cyt b )] and one nuclear gene ( RyR3 ). The higher haplotype diversity and moderate nucleotide diversity of wild large yellow croaker indicated that overexploitation, which caused a sharp decrease in biomass, did not lead to a loss of genetic diversity. According to phylogenetic construction and network analysis, the absence of a significant population structure pattern revealed a single panmictic population of wild large yellow croaker with exception of a population collected from the Sansha Bay, which showed high genetic relatedness to the cultured population, suggesting significant genetic effects resulting from stock enhancement. Overall, our study suggests no genetic differentiation in the entire wild population of large yellow croaker, which means that we have great flexibility in mixing and matching farmed and wild populations. However, since the result showed that domestication, the relaxation of purifying selection, increased genetic loads, and maladapted farmed fish will be at a selective disadvantage when cultured juveniles are released in the wild, the effectiveness of stock enhancement and the negative impact of hatchery-wild fish hybridization on the wild population must be carefully evaluated in future.